TAI Type Cooperative Learning Imroves Learning Achivement of Grade 6 Students At SD Negeri 2 Tawangsari - Mayasari, Asri (Universitas Sebelas Maret, 2022)
This study learns to learn the effectiveness of the Cooperative Type TAI (Team Assisted Individualization) learning model. From the results of the study conducted learning about conductors and insulators using the Cooperative Type TAI (Team Assisted Individualization) learning model. Specifically learning using the Cooperative Learning Model Type TAI (Team Assisted Individualization) further improves learning outcomes, the use of the Cooperative Type TAI learning model (Team Assisted Individualization) makes learning activities more enjoyable, students are actively involved and students who are learning to learn. In cycle I there were 4 people (36.36%) who were actively involved in learning and in cycle II it increased to 8 people (72.72%). Then student achievement also increased, this can be seen from the evaluation results, namely in cycle 1 the average score was 68.18 and in cycle II the average score was 84.54. This shows that student learning activities in science learning have increased. So it can be concluded that the TAI (Team Assisted Individualization) Cooperative learning model is effective for increasing student activity and achievement.